Deflected mode of marginal rock massif around mine working boundaries depending on anchoring parameters - Demin V. F.; Fofanov O. B. Oleg Borisovich; Demina T. V.; Yavorskiy V. V. (Information technologies in Mechanical Engineering, 2017)
Title screen